2021
DOI: 10.3390/w13020125
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Decision-Making Methods to Address Water Allocation Problems: A Systematic Review

Abstract: The water allocation problem is complex and requires a combination of regulations, policies, and mechanisms to support water management to minimize the risk of shortage among competing users. This paper compiles the application of multi-criteria decision-making (MCDM) related to water allocation. In this regard, this paper aims to identify and to discern the pattern, distribution of study regions, water problem classifications, and decision techniques application for a specific water allocation problem. We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 117 publications
0
21
0
1
Order By: Relevance
“…A more up-to-date (2020) but very short review can be found in [142]. For the specific topic of water allocation, MCDA methods were reviewed by [143] who noted that optimization methods based on the genetic algorithm [144] were the most frequently reported.…”
Section: Focus On Water Supplymentioning
confidence: 99%
“…A more up-to-date (2020) but very short review can be found in [142]. For the specific topic of water allocation, MCDA methods were reviewed by [143] who noted that optimization methods based on the genetic algorithm [144] were the most frequently reported.…”
Section: Focus On Water Supplymentioning
confidence: 99%
“…In this field, water policy evaluation, planning of water supply, selection of infrastructure have been the most common applications of MCDA before 2007 [67]. Water shortage problems, water use management, water quality problems and water allocation are recently primary topics for publications using MCDA methods [80].…”
Section: Multi-criteria Decision Analysis-analytic Hierarchy Process Approachmentioning
confidence: 99%
“…Water resources management in a basin has changed from a single-goal problem into more complex multi-criteria decision making (MCDM) problems, which involving multiple feature, multiple aspects, and multiple stakeholders Huang et al (2011); Gebre et al (2021); Hipel (1992); Hajkowicz and Collins (2007). Water is a fundamental resource for economic development, social welfare, and environmental protection.…”
Section: Introductionmentioning
confidence: 99%